Dynamic Interactions of Multiple Wall-Mounted Flexible Plates in a Laminar Boundary Layer - Zhang , Xiang; Li , Yuhang; Zhang , Xing (Frontiers in Physics, 2022)
The interactions between large arrays of wall-mounted flexible plates and oncoming laminar boundary-layer flows are studied numerically by using the immersed boundary method. The influences of bending rigidity, mass ratio and gap distance between adjacent plates on the dynamic behaviors are explored. With the variation of control parameters, five distinct dynamic modes, namely, static reconfiguration, sectional waving, regular waving, upright oscillation and cavity oscillation, are identified. The frequency lock-in phenomena and various types of flow instability associated with different dynamic modes are discussed. The findings of this study indicate that the coherent motions of the arrays are governed by a coupled mechanism in which the frequency of flow instability is locked onto the structural natural frequency.